PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA OPERASIONAL PADA LINGKUNGAN PERKANTORAN - Maritza Angela Kurnia Raharjo; Rizaldo Willy Syahroni; Retno Wahyuni (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The purpose of this study is to analyze the effect of compensation and motivation on operational performance in office environments. Utilizing a quantitative approach with a causal research design, the study examines data from 100 respondents selected through random sampling. Data collection was conducted via questionnaires distributed online, measuring variables of compensation, motivation, and operational performance using a Likert scale. Statistical analysis, including multiple linear regression, was employed to evaluate the relationships among the variables.The findings indicate that motivation has a more dominant and significant influence on operational performance compared to compensation. While compensation demonstrates a positive relationship with operational performance, its effect is statistically insignificant. The regression model reveals that both compensation and motivation collectively explain 16.26% of the variability in operational performance, suggesting that other factors also play substantial roles.These results underscore the importance of focusing on motivational strategies, such as recognition, career development opportunities, and a supportive work environment, to enhance employee performance. Although compensation remains a critical factor for retaining talent, its role should be complemented by initiatives aimed at fostering intrinsic and extrinsic motivation.